Experimental and Computational Studies on the Antiglaucoma Effects of Kelulut Honey (Heterotrigona itama) from Aceh in Rats (Rattus norvegicus) - Erlidawati*, Erlidawati; Rizarullah, Rizarullah; Mustika, Chessy Rima; Awlanur, Cut; Fazli, Rahmad Rizki; Saaid, Mardiana (Universitas Syiah Kuala, 2025)
This study aimed to evaluate the efficacy of kelulut (H. itama) honey as an antiglaucoma agent in rats. Kelulut honey diluted to a concentration of 400 ppm using distilled water was prepared for chemical and biological analysis. Secondary metabolites in the extracts were identified by phytochemical methods and antioxidant activity was evaluated by DPPH method. In vivo test was conducted on R. novergicus rats that had been treated with intraocular pressure with 5 treatment groups and 5 repetitions for the antiglaucoma test. In addition, in silico studies were also conducted using apigenin, cathecin, luteolin, naringenin and taxifolin against Rho Kinase protein. The results showed that kelulut honey extract has been confirmed to contain alkaloid, flavonoid, and flavone compound classes. The extract was also confirmed to have antioxidant activity with an IC50 value of 6.2 ppm against 5.4 ppm ascorbic acid. The findings showed that kelulut honey has efficacy as antiglaucoma in rats. The secondary metabolites in this honey, especially alkaloids, flavonoids, and flavones, showed high antioxidant activity (50). At a dose of 40 ppm, kelulut honey was showed to reduce intraocular pressure (IOP) by 46.56% in the right eye and 55.15% in the left eye of rats. This effect is comparable to the use of 2% pilocarpine. In silico study showed that all tested compounds have good binding affinity to protein targets, with promising key interactions. Therefore, kelulut honey was potentially a natural candidate for the development of antiglaucoma therapeutics.